Chromosome-level assembly of Pseudopodoces humilis genome: A resource for avian evolutionary studies - Xinwei Da; Yanrui Liu; Xun Jin; Xin Lu (Scientific Data)
Abstract Pseudopodoces humilis is a small passerine bird predominantly found in the mid-latitude regions of the Tibetan Plateau in Asia. A chromosome-level reference genome assembly for P. humilis was generated using PacBio CLR with Hi-C. The final genome assembly spans approximately 1.096 Gb, consisting of 1,968 contigs with a Contig N50 of 32.246 Mb, and was evaluated to be 95.60% complete using BUSCO. Hi-C chromosome mapping resulted in 33 chromosome sequences, which enabled the ordering and orientation of 329 contigs, with chromosome lengths ranging from 2.08 Mb to 152.13 Mb, covering 95.85% of the total genome sequence. Repetitive sequences comprised 144.91 Mb of the genome. A total of 381 tRNA, 507 non-coding RNA (ncRNA), and 205 rRNA were identified. In addition, we identified 17,108 protein-coding genes and 29,473 proteins, comprising a total of 17,236,726 amino acids. This high-quality genome assembly provides a strong genomic foundation for exploring critical questions in evolutionary genetics, phylogenomics, and the molecular mechanisms of adaptation - key areas for understanding biodiversity and species resilience amidst changing environments.